Risk of negative birth experience in trial of labor after cesarean delivery: A population-based cohort study - Lindblad Wollmann, Charlotte (PLoS One, 2020)
BACKGROUND: To improve care for women going through trial of labor after cesarean (TOLAC), we need to understand their birth experience better. We investigated the association between mode of delivery on birth experience in second birth among women with a first cesarean. METHODS: A population-based cohort study based on the Swedish Pregnancy Register with 808 women with a first cesarean and eligible for TOLAC in 2014–2017. Outcomes were mean birth experience measured by visual analogue scale (VAS) score from 1–10 and having a negative birth experience defined as VAS score ≤5. Linear and logistic regression analyses were performed with β-estimates and odds ratios (OR) with 95% confidence intervals (CI). RESULTS: Mean VAS score among women with an elective repeat cesarean (n = 251 (31%)), vaginal birth (n = 388 (48%)) or unplanned repeat cesarean (n = 169 (21%)) in second birth were 8.8 (standard deviation SD 1.4), 8.0 (SD 2.0) and 7.6 (SD 2.1), respectively. Compared to women having an elective repeat cesarean, women having an unplanned repeat cesarean delivery had five-fold higher odds of negative birth experience (adjusted OR 5.0, 95% CI 1.5–16.5). Women having a first elective cesarean and a subsequent unplanned repeat cesarean delivery had the highest odds of negative birth experience (crude OR 7.3, 95% CI 1.5–35.5). CONCLUSIONS: Most women with a first cesarean scored their second birth experience as positive irrespective of mode of delivery. However, the odds of a negative birth experience increased among women having an unplanned repeat cesarean delivery, especially when the first cesarean delivery was elective.